Epic and Empire in Nineteenth-Century Britain - Morroni, Mario (Cambridge University Press, 2013)
This book addresses, then, one particular understanding of epic in the nineteenth century, briefly summed up under the phrase ‘epic primitivism’. It pursues the consequences of this idea for the meaning of a national poetry in Britain, for the translation of epic, for the possibility of writing a national epic and for the conception of empire and its subject peoples